Role of COVID-19 infection status on the prediction of future infection: Immunity or susceptibility - Fateme Nikbakht; Hamid Heidarian Miri; Ehsan Mosafarkhani; Fatemeh Sharifjafari; Ali Taghipour (PLoS ONE, 2025)
Background COVID-19 has rapidly spread around the world, and the duration of protective immunity against the virus remains unknown. Evidence suggests that patients with a confirmed COVID-19 infection may experience reinfection. The aim of this study is to determine the relationship between COVID-19 reinfection and previous infection history in the population covered by Mashhad University of Medical Sciences. Methods This population-based, historical cohort study included all individuals with health records at the health service centers of Mashhad University of Medical Sciences who underwent PCR testing during the study period (April 1, 2020, up to February 19, 2022). The data were analyzed by calculating the infection rate in both PCR-positive and negative individuals, and estimating the adjusted rate ratio using Poisson regression. Results The results of this study in the entire population showed that the incidence rate in people with a history of primary COVID-19 infection was 13% higher than that in people who had no history of this disease. However, in the group that received the vaccine prior to the first PCR test, the incidence rate was lower among individuals with a positive first test result (IRR =  0.71) compared to those with a negative first test result. Conclusion The study reveals that prior COVID-19 infection does not ensure immunity and may increase the risk of reinfection, particularly among men and younger individuals. Vaccination appears to complicate this dynamic, as those with multiple vaccine doses showed higher reinfection rates compared to those with fewer doses. These findings highlight the need for ongoing research and tailored public health strategies to address the complexities of COVID-19 immunity and reinfection.